The Mistaken Birth and Adoption of LNT: An Abridged Version - Edward J. Calabrese (SAGE Publishing, 2017)
The historical foundations of cancer risk assessment were based on the discovery of X-ray-induced gene mutations by Hermann J. Muller, its transformation into the linear nonthreshold (LNT) single-hit theory, the recommendation of the model by the US National Academy of Sciences, Biological Effects of Atomic Radiation I, Genetics Panel in 1956, and subsequent widespread adoption by regulatory agencies worldwide. This article summarizes substantial recent historical revelations of this history, which profoundly challenge the standard and widely acceptable history of cancer risk assessment, showing multiple significant scientific errors and incorrect interpretations, mixed with deliberate misrepresentation of the scientific record by leading ideologically motivated radiation geneticists. These novel historical findings demonstrate that the scientific foundations of the LNT single-hit model were seriously flawed and should not have been adopted for cancer risk assessment.